576 Clinical characterization of insomnia disorder in adolescence. (3rd May 2021) - Yuksel, Dilara; Prouty, Devin; Kiss, Orsolya; Volpe, Laila; Arra, Nicole; Dulai, Teji; Durley, Ingrid; Obilor, Todd; Baker, Fiona; de Zambotti, Massimiliano
Abstract: Introduction: Insomnia is common in adolescence, particularly in older girls, with an overall prevalence comparable to major depression. Despite being associated with adverse outcomes such as an increased risk for substance dependence and suicidality, insomnia in adolescence is still under-recognized, under-diagnosed, and under-treated, and poorly described in the literature. This study aims to investigate the clinical features of insomnia in adolescence, in both boys and girls. Methods: Eighty-five post-pubertal adolescents (16–18 years) with (N=39, 26 girls) and without (N=46, 28 girls) DSM-5 insomnia symptoms underwent a detailed clinical evaluation, including a clinical interview with a trained clinician and an extensive questionnaire battery investigating sleep behaviors, stress, coping skills, emotion regulation, mood, and personality traits. Results: Adolescents with insomnia symptoms exhibit poorer sleep and sleep-related behaviors, such as higher insomnia severity scores, lower sleep hygiene, higher dysfunctional beliefs and attitudes about sleep, and higher pre-sleep negative thought content compared with controls (p<0.05). They also indicated higher stress levels associated with school performance and peer pressure, higher susceptibility to work overload and greater depressive symptoms than controls (p<0.05). Insomnia girls reported a lower perceived sleep quality, higher perceived stress levels, and a higher sleep vulnerability to stress than insomnia boys (p<0.05). Exploratory network analyses unveiled profound group differences in the extent of multi-symptoms' interconnection, with network complexity being lower in adolescents with insomnia symptoms and showing distinct symptoms' centrality and clustering. Conclusion: Insomnia in adolescence needs to be considered in the context of both classical insomnia-related features, as well as adolescence-specific factors, such as school and peer stress. Network analysis may be a promising approach to unveil hidden relationships and patterns among insomnia symptoms and behaviors, and to better characterize insomnia, possibly advancing early recognition and treatment of the disorder. Support (if any): National Heart, Lung and Blood Institute (NHLBI) R01HL139652 (to MdZ)